Treatment With Propranolol for Infantile Hemangioma in 13 Taiwanese Newborns and Young Infants - Teng-Chin Hsu; Jiaan-Der Wang; Chao-Huei Chen; Te-Kau Chang; Teh-Ming Wang; Chia-Man Chou; Heng-Kuei Lin (Elsevier, 2012)
Hemangioma in infants has a benign self-limited course, but the 10% of cases with complications need further treatment. Successful treatment with propranolol in western countries has been reported over the past few years. We evaluated the efficacy of propranolol for treating infantile hemangioma in Taiwanese newborns and young infants. Methods: Patients below 1 year of age treated with propanolol between November 2009 and March 2011 were enrolled. Demographic data, clinical features, imaging findings, treatment regimens of propranolol, and outcome were investigated. Results: Thirteen patients were treated with propranolol at a dose of 2-3 mg/kg/day. Seven (53.8%) patients had solitary hemangioma and six had multiple ones. The indications for treatment were risk of local event in nine patients, functional risk in four, local complication in one, and life-threatening complication in one. The median age for starting propranolol was 4 months (range: 1-11 months). Responses to propranolol, such as decolorization, regression in tumor size, or improvement of hemangioma-associated complications were observed in all patients within 1-2 weeks after treatment. Propranolol-associated adverse effects occurred in two patients. One infant had occasional tachypnea, and the other had occasional pale-looking appearance. The symptoms resolved after dosage tapering. Conclusion: Propranolol may be a promising therapeutic modality for infantile hemangioma. Therapeutic strategies are needed to evaluate the optimal treatment protocol and long-term adverse effects.